Information Literacy Instructional Practices Among Academic Librarians Within the Asia and Asia-Pacific Region: A Comparative Analysis - Dayang Norsheila, Abang Mohtar; Fitri Suraya, Mohamad (2023)
This study examined the level of understanding needed by academic librarians working at university libraries in Asia and Asia-Pacific to produce practical teaching skills in Information Literacy (IL) courses. Data were analysed using Braun and Clarke's 2006 thematic analysis approach. Respondents were those teaching IL at five universities in Malaysia, one in Singapore, and one in New Zealand. Analysis indicated stark differences in how IL is taught in all participating universities. The findings helped identify the challenges faced by librarians as a result of the behavioural change brought about by 21st-century learners in higher education institutions which led respondents to question their teaching efficacy and how their work as informed instructors in delivering IL module content to students have informed the shifting roles of academic librarians in teaching IL.